A new species of the genus Hylcalosia from China (Hymenoptera: Braconidae: Alysiinae) - Li, Jimin; Wang, Lingmin; Chen, Jiahua; Yu, Shenkai; Yao, Junli (Zootaxa, 2021)
Hylcalosia Fischer, 1967, is a small braconid genus with 18 described species from the Oriental and Palaearctic regions. A new species, Hylcalosia yongjingzengi Yao n. sp. from Wuyi Mountain Nature Reserve, Fujian, China is described and illustrated. A key to all known species of the genus Hylcalosia is presented.